PRIMARY SCHOOL TEACHERS SELF REFLECTION TRAINING TO IMPROVE TEACHER PROFESSIONALISM (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
This article discusses self-reflection training for elementary school teachers that is closely related to the call of the soul of elementary school teachers to be more professional in carrying out their duties as teachers. A person's interest in the teaching profession will make him work happily and feel responsible. Interest is not enough to become an elementary school teacher, but the calling of the soul as a teacher is needed. How can you keep an elementary school teacher's interest and vocation? One way is reflection. What is reflection? Reflection is a way of reflecting on the experience gained in order to improve itself in order to live better. With reflection, elementary school teachers will get to know themselves more so that they can communicate with students who are in desperate need of attention from their teacher. When someone becomes an elementary school teacher and in accordance with his soul call, then all thoughts and wills are focused on developing his students. Sometimes someone who works as an elementary school teacher does not have a call and interest as a teacher. This is evident by the transfer of the teacher to other professions because he considers the teacher to be a promising profession. Besides that there is also a teaching profession which is only considered as a stepping stone before getting a job. We can imagine the character of children who are educated by teachers who do not love them. Reflection training held on an ongoing basis will make elementary school teachers get to know themselves so that the calling of their souls and interests is increasingly fostered so as to improve their professionalism as elementary school teachers.